Integrating Neurolaw in Environmental Crimes and Strengthening Victim Protection in Criminal Liability Discourse - Fernando, Zico Junius; Kusumah, Fardana (Universitas Sultan Ageng Tirtayasa, 2025)
The increasing complexity of environmental crimes, often perpetrated by corporate actors and facilitated through systemic negligence, has challenged traditional models of criminal responsibility. While conventional criminal law relies on the assessment of mens rea the subjective mental element of guilt this approach often proves inadequate in addressing the nuanced realities of environmentally harmful behavior, which may arise from collective decision-making, cognitive impairments, or moral disengagement. In response, the emerging field of neurolaw introduces neuroscientific insights into legal reasoning, offering an interdisciplinary perspective on how neurological conditions and cognitive processes influence criminal culpability. This research explores the potential of integrating neurolaw into the adjudication of environmental crimes, particularly in evaluating criminal liability in cases involving indirect or diffuse intent. Through normative legal analysis, statutory and conceptual approaches, and comparative reflection on practices in jurisdictions such as the United States, Italy, Germany, and Brazil, the study investigates how neurocognitive evidence such as functional brain imaging and neuropsychological evaluations may complement existing doctrines in Indonesian criminal and environmental law. The analysis includes a critical examination of Indonesia’s Criminal Code (KUHP), Law No. 32/2009 on Environmental Protection and Management, and the principle of strict liability, assessing their compatibility with a neurolaw-informed framework. Importantly, this research also emphasizes the need to strengthen victim protection in the discourse of environmental criminal liability. While neurolaw has been primarily applied to analyze the cognitive condition of offenders, it must not obscure the rights of victims both human and ecological. The study argues for a balanced approach that incorporates neuroscientific considerations without undermining justice for affected communities, future generations, or non-human victims of ecological harm. By aligning neurolaw with victim-centered environmental justice principles, the research proposes a more holistic model of criminal accountability that advances fairness, scientific integrity, and ecological restoration.